2021
DOI: 10.1002/jez.2541
|View full text |Cite
|
Sign up to set email alerts
|

Take time to look at the fish: Behavioral response to acute thermal challenge in two Amazonian cichlids

Abstract: Critical thermal maximum (CTmax) is often used as an index of upper thermal tolerance in fishes; however, recent studies have shown that some fishes exhibit agitation or avoidance behavior well before the CTmax is reached. In this study, we quantified behavioral changes during CTmax trials in two Amazonian cichlids, Apistogramma agassizii and Mesonauta insignis. The thermal agitation temperature (Tag) was recorded as the temperature at which fish left cover and began swimming in an agitated manner, and four be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
(102 reference statements)
2
9
0
Order By: Relevance
“…Our finding that embryos exhibited a period of increased activity, which peaked approximately 2-3°C before CTmax, is in line with the theory that ectotherms may exhibit behavioural strategies to avoid physiological damage that occurs near their CTmax (Kochhann et al, 2021;Lutterschmidt & Hutchison, 1997). These behavioural strategies may be associated with seeking local thermal refugia or alternative habitats (Kochhann et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our finding that embryos exhibited a period of increased activity, which peaked approximately 2-3°C before CTmax, is in line with the theory that ectotherms may exhibit behavioural strategies to avoid physiological damage that occurs near their CTmax (Kochhann et al, 2021;Lutterschmidt & Hutchison, 1997). These behavioural strategies may be associated with seeking local thermal refugia or alternative habitats (Kochhann et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Our results are in line with other quantitative studies, for example an increase in activity was observed 6°C before CTmax in the neotropical cichlid Cichlasoma paranaense (Brandão et al 2018). In adult Amazonian cichlids Apistogramma agassizii and Mesonauta insignis, Tag was observed at 4 and 5.4°C, respectively, prior to CTmax (Kochhann et al, 2021). It is worth noting that all embryos in a trial in our study continued to be heated until no movements and no heartbeats were observed in any individuals in the trial.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…For example, Pagurus bernhardus in low pH significantly reduced antennular flick rates (the ‘sniffing’ response in decapod) and movement [ 13 ]. In the increased temperature, Apistogramma agassizii and Mesonauta insignis increased both activity level and digging behavior and decreased the use of shelter [ 14 ]. Additionally, the salinity in water is always changing due to tidal action and seasonal variation, forcing aquatic animals to start osmotic regulation to reach a new equilibrium [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%